PRESERVING BIODIVERSITY AND AGROECOSYSTEM OF COCOA CROPS - Martiningsih, Ni Gst. Ag. Gde Eka; Suryana, I Made; Javandira, Cok; Leu, Yohanes (International Journal of Research -GRANTHAALAYAH, 2020)
Agroecosystem in cocoa plant was once of the important thing that have to manage intend to make the cacao plantation sustain. Cocoa was the mascot of industrial plant trade in Bali Province including in Tabanan Regency. Cocoa cultivation is almost done by most plantation farmers in Bali. The Bali Government, through the Tabanan Food and Agriculture Office, strongly supports the spread of cocoa cultivation. In 2010, a free seedling assistance policy for farmers was issued in order to obtain uniformity of growth and yield of cocoa plants. The types of cocoa cultivated by farmers vary, so that since 2015 there have been stunting and of cocoa pod rot (CPB). Several studies on cocoa have been carried out, but they have not been able to provide solutions to disease attacks, especially cocoa pod rot. In this regard, this study was conducted to provide solutions in terms of cocoa crop management in order to know how to reduce the percentage of damage to cocoa plants and determine the strategies to manage the Cocoa plant in field. This research shows that the best strategy to reduce the pod rot in cocoa plant is pruning the branch of cocoa. The pruning activity is useful to make the area of cocoa plant well maintained and clean.